Efficacy and cognitive side effects of electroconvulsive therapy (ECT) in depressed elderly inpatients with coexisting mild cognitive impairment or dementia - Hausner, Lucrezia; Damian, Marinella; Sartorius, Alexander; Frölich, Lutz (The journal of clinical psychiatry, 2010)
Article AbstractObjective: To study cognitive performance in depressed geriatric inpatients with or without preexisting cognitive impairment who received a first course of electroconvulsive therapy (ECT).Method: Forty-four elderly inpatients with major depressive disorder (ICD-10 criteria) were included in a prospective consecutive case series of a university hospital. The patients were divided into 3 groups (no cognitive impairment , mild cognitive impairment , dementia) and rated for cognitive performance with the MMSE before first ECT, after sixth ECT, and 6 weeks and 6 months after ECT termination. Affective symptoms were rated by 21-item Hamilton Depression Rating Scale (HDRS-21) before and 6 weeks after ECT. Analysis of variance or Kruskal-Wallis tests on ECT-induced MMSE and HDRS-21 score changes were compared to baseline. Binary logistic regression was used for predictor analysis. The study was conducted from April 2004 to April 2008.Results: After initial nonsignificant cognitive deterioration in all 3 groups, the NCI group improved cognitively 6 weeks (P = .018) and 6 months (P = .027) after ECT. The MCI group improved in cognition 6 months (P = .036) after ECT. In the dementia group, mean MMSE scores also improved numerically over the course of ECT without significance. Dementia patients with antidementia treatment improved in cognition to a clinically relevant extent after the sixth ECT. Dementia subjects without antidementia treatment deteriorated. After the sixth ECT, 70.0% of dementia patients (P = .004) presented a cognitive decline, and 68.8% of MCI patients (P < .001) presented a decline 6 weeks after ECT. Six months after ECT, one-third of the dementia patients (P < .036) still had a cognitive decline. Affective symptoms remitted after ECT in all 3 groups (P < .001). Pre-ECT cognitive deficits were the best predictor of MMSE decline (6 weeks after ECT, P = .007; 6 months after ECT, P = .055).Conclusions: ECT is effective and well tolerated in geriatric depressed inpatients regardless of preexisting cognitive impairment. Cognitive deficits were transient.J Clin PsychiatrySubmitted: January 11, 2010; accepted April 12, 2010.Online ahead of print: November 30, 2010 (doi:10.4088/JCP.10m05973gry.Corresponding author: Lucrezia Hausner, Dr Med, Central Institute of Mental Health, Sq J5, D-68159 Mannheim, Germany (Lucrezia.hausnergmx.de).
Gesehen am 23.09.2022